Beyond inhibition: GABA synapses tune the neuroendocrine stress axis. (19th March 2014) - Inoue, Wataru; Bains, Jaideep S.
<x xml:space="preserve">Abstract</x> We recently described a novel form of stress‐associated bidirectional plasticity at GABA synapses onto hypothalamic parvocellular neuroendocrine cells (PNCs), the apex of the hypothalamus‐pituitary‐adrenal axis. This plasticity may contribute to neuroendocrine adaptation. However, this GABA synapse plasticity likely does not translate into a simple more and less of inhibition because the ionic driving force for Cl−, the primary charge carrier for GABAA receptors, is dynamic. Specifically, stress impairs a Cl− extrusion mechanism in PNCs. This not only renders the steady‐state GABA response less hyperpolarizing but also makes PNCs susceptible to the activity‐dependent accumulation of Cl−. Accordingly, GABA synapse plasticity impacts both the robustness of GABA voltage response and dynamic Cl− loading, imposing nonlinear influences on PNC excitability during circuit activities. This theoretical consideration predicts roles for GABA transmission far more versatile than canonical inhibition. We propose potential impacts of GABA synapse plasticity on the experience‐dependent fine‐tuning of neuroendocrine stress responses.